2022
DOI: 10.1155/2022/8669941
|View full text |Cite
|
Sign up to set email alerts
|

SKIA-SH: A Symmetric Key-Based Improved Lightweight Authentication Scheme for Smart Homes

Abstract: Being one of the finest applications of the IoT, smart homes (SHs) with an aim to improve quality of life are taking over the traditional lifestyles. The entities within a SH communicate with each other and with the environment including the users to transform daily life seamlessly enjoyable and easy. However, owing to the public communication infrastructure, the advantages of SH are subject to security and privacy issues. Recently, Yu et al. presented a privacy and security solution for SH environment. The sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Outcomes display that our suggested scheme including the key exchange process consumed less estimated communication cost as compared to other existing schemes. Our proposed scheme reduced communication costs by up to 25.28 % compared to [33].…”
Section: B Communication Overhead Comparisonsmentioning
confidence: 98%
See 2 more Smart Citations
“…Outcomes display that our suggested scheme including the key exchange process consumed less estimated communication cost as compared to other existing schemes. Our proposed scheme reduced communication costs by up to 25.28 % compared to [33].…”
Section: B Communication Overhead Comparisonsmentioning
confidence: 98%
“…Similarly, in [29]- [33], researchers proposed authentication schemes for IoT-based smart home environments. The proposed schemes adopt very complex procedures for key exchange and authentication processes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Zou et al [18] devised a more secure scheme. Yu et al [17] devised a three factor AKA scheme, but Alzahrani et al [45] found that Yu et al's scheme [17] cannot provide mutual authentication. Piraytesh et al [21] proposed a hyperelliptic curve cryptosystem-based AKA scheme in smart home, which they claim ensures good performance.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, Yu et al [ 18 ] found that the protocol of Kaur and Kumar [ 38 ] could not resist impersonation attacks and session key disclosure attacks and proposed a secure AKA protocol based on three factors. However, Alzahrani et al [ 39 ] discovered that Yu et al’s protocol [ 18 ] was unable to achieve mutual authentication. Banerjee et al [ 40 ] found that Shuai et al’s protocol [ 37 ] could not resist stolen smart card attacks and user impersonation attacks and then proposed an efficient anonymous authentication protocol.…”
Section: Related Workmentioning
confidence: 99%